Analisis kadar vitamin C velva kombinasi buah lokal jambi: Nanas tangkit dan jeruk gerga - Putri, Satiti Kawuri; Pasca, Bella Dwi; Maharani, Putri; Rizki, Tri; Suseno, Rahayu; Anggraini, Anna; Sevina, Raisa; Anggraini, Rani (Proceedings Academic Universitas Jambi, 2025)
Velva is a processed food product made from fruit pulp that is frozen to form an ice cream-like texture. The use of local fruits such as Gerga oranges (Citrus grandis var. Kerinci) and Tangkit pineapples (Ananas comosus), which are rich in vitamin C and antioxidants, also adds value in diversifying processed food products in Jambi Province. This study aims to determine the vitamin C content of Velva from a combination of Tangkit Pineapple and Gerga Orange. This study uses three treatments comparing the ratio of Tangkit Pineapple and Gerga Orange. The treatments in this study consisted of P1 (40 g Tangkit pineapple : 60 g Gerga orange), P2 (50 g Tangkit pineapple : 50 g Gerga orange), and P3 (60 g Tangkit pineapple : 40 g Gerga orange). The data were analyzed descriptively to determine the vitamin C content between treatments. The results showed that the more Tangkit pineapple added, the lower the vitamin C content.